In plants the alc gene expression system responds more rapidly following induction with acetaldehyde than with ethanol - Sonnewald, Uwe; et al. (Febs Letters, 2003)
It has recently been proposed that acetaldehyde is the physiological inducer of the alc gene system and hence indirectly the activator of the AlcA promoter in Aspergillus nidulans. Here we show that this chemical induces expression of a GUS (beta-D-glucuronidase) reporter under the control of the alc gene system in transgenic potato tubers more rapidly than ethanol allowing tighter control of transgene expression. Furthermore by analysis of metabolite levels we demonstrate that the application of inducer has few effects on metabolism. We propose that this system is therefore ideal for the temporal regulation of important metabolic enzyme activities. (C) 2003 Federation of European Biochemical Societies. Published by Elsevier Science B.V. All rights reserved.
Keywords: chemical inducer; gene expression; metabolism; ethanol; acetaldehyde